Species of Neohaliotrema Yamaguti, 1965 (Monogenea: Ancyrocephalidae) from the pomacentrid Abudefduf vaigensis (Quoy & Gaimard) off Pulau Langkawi, Malaysia, with a revised diagnosis of the genus and a key to its species - Lim, L.H.S.; Gibson, D.I. (Kluwer (now part of Springer), 2010)
Four new and one unidentified species of Neohaliotrema Yamaguti, 1965 were obtained from the gills of the Indo-Pacific sergeant Abudefduf vaigensis (Quoy & Gaimard) off Pulau Langkawi, Malaysia. The five species, N. malayense n. sp., N. bombini n. sp., N. andamanense n. sp., N. parvum n. sp. and an unidentified Neohaliotrema sp. (similar to N. macracanthum Zhukov, 1976), are described and distinguished based mainly on features of the haptor. Species of this genus are divisible into two groups, the `maomao group', with two pairs of morphometrically modified `marginal' hooks and a fenestrated haptor, and the `gracile group', with morphologically similar marginal hooks and an entire haptor. With the exception of N. bombini n. sp., the species described fit within the `maomao group'. It is suggested that the more complex Neohaliotrema species of the `maomao group' have modified hooks 1 and 2 on a haptoral `isthmus' between two large apertures, i.e. `windows', whereas the less complex species lacking these features are those of the `gracile group'. Neohaliotrema spp. have only a single pair of pigmented eye-spots. A fenestrated haptor is unique to the Neohaliotrema spp. of the `maomao group'. The generic diagnosis of Neohaliotrema is amended to include new data and a key to its known species is presented.